Overview of hydrological and climatic studies in Africa: The case of Ghana. Issue 1 (1st January 2021) - Ampadu, Boateng
Abstract: Climatic impacts on the environment, land cover and land use change such as urbanisation and deforestation affect rainfall and change riverflow responsiveness and seasonal flows as a result of their influence on nonlinear behaviour of the catchments of rivers. Water supply is seriously affected which invariably impacts on domestic activities and agriculture. In some countries river transportation, hydropower, irrigation and fish farming are at risk due to these impacts. Within this paper, a review of existing hydrological and climatic studies in Africa and Ghana in particular is presented. The paper highlights the knowledge gaps identified in the review, such as rainfall-riverflow processes and their controls in the country, estimation of cycles in evapo-transpiration and solar radiation time series, together with the complete characterisation of the temporal and spatial fluctuations within the climate cycles. The establishment of a monograph of catchment response characteristic across the Ghanaian latitudinal gradient and if possible across the tropics is recommended. This could be used for the prediction of hydrologic response of ungauged catchments in the country.